Protective Effects of Dexmedetomidine on Sepsis-Induced Vascular Leakage by Alleviating Ferroptosis via Regulating Metabolic Reprogramming - She H; Hu Y; Zhou Y; Tan L; Zhu Y; Ma C; Wu Y; Chen W; Wang L; Zhang Z; Wang L; Liu L; et al. (Dove Medical Press, 2021)
Han She,1,2,* Yi Hu,1,* Yuanqun Zhou,2 Lei Tan,1 Yu Zhu,2 Chunhua Ma,2 Yue Wu,2 Wei Chen,1 Li Wang,2 Zisen Zhang,2 Li Wang,1 Liangming Liu,2 Tao Li2 1Department of Anesthesiology, Daping Hospital, Army Medical University, Chongqing, 400042, People's Republic of China; 2State Key Laboratory of Trauma, Burns and Combined Injury, Second Department of Research Institute of Surgery, Daping Hospital, Army Medical University, Chongqing, 400042, People's Republic of China*These authors contributed equally to this workCorrespondence: Liangming Liu; Tao Li Email liangmingliu@yahoo.com; Lt200132@163.comIntroduction: Vascular leakage plays a vital role in sepsis-induced multi-organ dysfunction. Currently, no specific measures are available for vascular leakage. Ferroptosis, as a recently recognized form of cell death, plays a crucial role in cell dysfunction. It is still unknown whether ferroptosis participates in the occurrence of organ dysfunction following sepsis. Our previous study showed that dexmedetomidine (Dex) could alleviate sepsis-induced organ dysfunction. However, whether the mechanism is related to ferroptosis is not clear.Methods: The publicly available datasets of septic patients were reanalyzed, and septic models in vivo and vitro by cecal ligation and puncture and lipopolysaccharide-stimulated vascular endothelial cells (VECs) were applied. The occurrence of ferroptosis in septic patients and rats was observed, and the protective effects of Dex on ferroptosis, and related mechanisms on regulating metabolic reprogramming and mitochondrial fission were further studied.Results: The transcriptomics data of patients from the GEO database showed that ferroptosis was closely related to sepsis. Sepsis induced significant ferroptosis in VECs by metabolomics analysis. The level of lipid peroxidation was increased in VECs, and the mitochondrial cristae was decreased after sepsis. Metabolomics analysis showed that Dex activated the pentose phosphate pathway and increased glutathione in VECs via up-regulation of G6PD expression. Dex could antagonize sepsis-induced the decrease in the level of Nrf2. The Nrf2 inhibitor reversed the protective effect of Dex on ferroptosis. Further study showed that Dex significantly alleviated sepsis-induced mitochondrial over-division, improved mitochondrial function, and decreased ROS, further inhibiting the ferroptosis of VECs. Dex alleviated the permeability of vessels by reducing ferroptosis and enhanced the intercellular junction of VECs.Conclusion: Dex protects vascular leakage following sepsis by inhibiting ferroptosis. The mechanism is mainly related to metabolic reprogramming via Nrf2 up-regulation and inhibition of mitochondrial fission.Keywords: dexmedetomidine, sepsis, ferroptosis, metabolic reprogramming, mitochondrial fission